2007
DOI: 10.1093/jae/ejm004
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mortality in Uganda: Determinants, Trends and the Millennium Development Goals

Abstract: We are grateful to David Sahn and Peter Glick for comments. This research is supported by SAGA, a cooperative agreement between USAID and Cornell and Clark-Atlanta Universities. See www.saga.cornell.edu. AbstractUnusually for an African economy, Uganda's growth has been rapid and sustained for an extended period of time. Further, this growth has clearly translated into substantial declines in poverty for all socio-economic groups and in all regions of the country. Despite this, there is concern in the country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 6 publications
4
20
0
Order By: Relevance
“…Children born after a short interval to the previous birth generally present higher mortality risks (Manda, 1999). Many studies have reported that males have higher mortality rates at all ages of childhood (Hill and Upchurch, 1995;Lavy et al 1996;Ssewanyana and Younger, 2007). Similar evidence on the effects of biodemographic factors have been provided by Nigerian studies (Adewuyi and Feyisetan, 1988;Ahonsi, 1995;Lawoyin, 2007).…”
Section: Biodemographic Factorsmentioning
confidence: 56%
“…Children born after a short interval to the previous birth generally present higher mortality risks (Manda, 1999). Many studies have reported that males have higher mortality rates at all ages of childhood (Hill and Upchurch, 1995;Lavy et al 1996;Ssewanyana and Younger, 2007). Similar evidence on the effects of biodemographic factors have been provided by Nigerian studies (Adewuyi and Feyisetan, 1988;Ahonsi, 1995;Lawoyin, 2007).…”
Section: Biodemographic Factorsmentioning
confidence: 56%
“…Increasing the rate of vaccination to 100% was considered the most influential and probably most costeffective intervention, reducing infant deaths by 16 per 1000 births. 35 Other high-impact child survival interventions shown to quickly reduce mortality include appropriate treatment of childhood diarrhea and pneumonia. 4 Our study demonstrates the need for additional research into the mechanisms by which economic factors affect child mortality in lowincome countries, to encourage policies and interventions that will effectively reduce preventable child deaths.…”
Section: Figurementioning
confidence: 99%
“…Evidence has shown that household income affect child mortality negatively. For example, Ssewanyana and Younger (2004) found that in Uganda higher household income and infant mortality were negatively correlated. This may be explained by the fact that wealthier households have the capacity to provide good nutrition, shelter and health care services for children.…”
Section: Introductionmentioning
confidence: 99%